The effects of teaching strategies on learning to think critically in primary and secondary schools: an overview of systematic reviews [version 2; peer review: 2 approved] - Margaret Kaseje; Andrew D. Oxman; Allen Nsangi; Sarah E. Rosenbaum; Heather Munthe-Kaas; Laura Martínez García; Daniel Semakula; Laura Samsó Jofra (F1000Research)
Background We conducted an overview of systematic reviews about the effects of teaching strategies that can be used to teach primary and secondary school students to think critically. Our objective was to inform decisions about what teaching strategies to use in resources that we developed to teach critical thinking about health in secondary schools. Methods We mapped characteristics of systematic reviews of teaching strategies and summarised findings from the most relevant reviews to teaching students to think critically about health. We included reviews that assessed the effects of teaching strategies that could potentially be used in primary or secondary schools to teach students to think critically, had a Methods section with explicit selection criteria, reported at least one outcome measure of the ability to undertake one of four basic types of cognitive tasks (memory, procedural, comprehension, or opinion), and were published after 1999. Results We included 326 systematic reviews. The reviews evaluated a wide range of teaching strategies for a variety of purposes. Important limitations of the reviews included not considering adverse effects (99% of the reviews), not assessing the risk of bias for included studies (93% of the reviews), and not assessing the credibility of subgroup effects (100% of the reviews). We summarised the findings for 37 teaching strategies that we considered most relevant. The certainty of the evidence of the effects varied from very low to moderate. We used 12 of the strategies in resources that we developed to teach secondary students to think critically about health. Conclusions A tremendous amount of work has gone into evaluating the effects of a wide range of teaching strategies. The results of this research can inform decisions about how to teach critical thinking and future research. However, well-designed, up-to-date systematic reviews are still needed for many teaching strategies.